Venezuela’s accession and institutional management of asymmetries in MERCOSUR - Cimadamore, Alberto D. (2013)
The Accession Treaty signed by Venezuela with MERCOSUR in 2006 adopts the principles of gradualism, flexibility, equilibrium, recognition of the asymmetries and differential treatment. Asymmetries can cause negative externalities, as well as they may have the potential to promote the process in a dialectical manner. This is one of the theoretical premises that guides this article. In this work we will analyze the characteristics of the asymmetries in MERCOSUR, how the admission of Venezuela affects this situation, the treatment given to the asymmetries in MERCOSUR vis à vis the EU, and the type of institutions that deals with the asymmetries in the MERCOSUR.